ANTIBIOTIC- ASSOCIATED RISK THE REDUCTION OF LACTOBACILLUS SPP. IN THE INTESTINAL MICROBIOTA IN PATIENTS WITH URINARY TRACT INFECTIONS - Stepanova, N.; Stashevska, N.; Lebid, L.; Savchenko, S.; Kolesnyk, M. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim of our study was to evaluate a risk reduction of indigenous gut microbiota in patients with urinary tract infection (UTI, associated with the intake of antibacterial medicinal products Materials and methods. To this retrospective cohort case-control study were involved 233 women with UTI. The mean age in the patient population was 36.7 ± 15.6 years. Cases were defined as reducing the number of Lactobacillus spp. < 10 million colony forming units in 1 g offeces (mln. CFU/g). We evaluated the daily urinary oxalate excretion and bacteriological seeding feces. Investigational antibiotics were medicines which are generally used to treat the outpatient with UTI. Results. The data analysis demonstrated an extremely high risk the reducing of Lactobacillus spp. colonization in the patient’s intestine. The use of ciprofloxacin was significantly associated with an availability of hyperoxaluria ( = 0.31, p = 0.008). Conclusions. Thus, the use of antibacterial medicinal products, even in prophylactic doses, by the patients with UTI leads to the destruction of the normal composition of gut microbiota, and, primarily, due to the fact that the content of Lactobacillus spp. is deceased.